Micropropagationof Male and Female Trees of Andaleh (MorusmacrouraMiq.) through In-vitro Culture using Several Compositionsof Basal Medium - Aswaldi Anwar (Department of Crop Science, Faculty of Agriculture, Andalas University, 2018)
Andalehis the local name of MorusmacrouraMiq. in West Sumatra, Indonesia. Nowadays, this dioeciously speciesis in endangered situation. The aim of the research is to find out the appropriate combination of plant growth regulator to induce shoot multiplication of explants from male and female trees of andaleh. The plantlets from this research will be used in the next future to conserve this endangered species in vitro and in vivo, especially in preparing parental material in breeding program. Young buds from male and female trees were used as an explants in basal medium Murashige and Skoog supplemented with BAP (0.5, 1.0, 1.5 and 2.0 mg.L-1) in combination with NAA (1.0 mg.L-1 for each). The frequency of bud break was 50 % in MS medium supplemented with BAP (0.5 mg.L-1) and NAA 1.0 mg.L-1 for both source of explants (female and female trees of andaleh) after 3 weeks of culture. Generally, the number of shoot induction was very low. On the other hand, the rate of callus formation was high (100%) in highest BAP concentration (2.0 mg.L-1).